The psychological after-effects of COVID
1 online resource
Keywords: "This comprehensive resource provides a one-stop information repository, exploring all psychological aspects of Covid-19. It documents the after-effects of the Covid pandemic, and how it transformed India as a society and its citizens as individuals. The book covers the psycho-social impact on society and individuals and our collective behaviour, as well as coping strategies and interventions and how lessons learned will help in preparedness for the future. Including case studies and the latest research, this book examines how psycho-social paradigms changed as a result of the pandemic, and left their watermark on the human psyche. It also explores the coping strategies adopted to deal with this common aggressor and how the techniques varied in accordance with social, cultural and geographical factors. The final chapters offers new insights for the future, highlighting the psychological infrastructure required, the type of preparedness and handling strategies necessary to mitigate the impact of any future biogenic pandemics. Combining theory and practical application, it will be valuable reading for academics and researchers as well as practising psychologists, clinical psychologists and law-makers who are concerned with mental health"--